Hubungan Antara Komitmen Religiusitas Dengan Loyalitas Kerja Karyawan - Syfa, Nadya; , Drs. Mohammad Amir, M.Si (2017)
Correlation Between Commitment Religiosity With Employee Loyalty ABSTRACT Job loyalty is a situation that concerns physical, psychological and social activities so that humans have a strong sense of ownership and responsibility and involve themselves to contribute efforts to achieve organizational goals. One of the factors that affect work loyalty is to pay attention to spiritual needs. This study aims: (1) To determine the relationship between religiosity with employee loyalty; (2) To know the contribution of religiosity to employee work loyalty; (3) To know the condition of religiosity; (4) To know the condition of work loyalty. The hypothesis proposed is there is a positive relationship between religiosity with employee loyalty in Hotel Syariah Aziza Solo. Research population are 65 employees working in the field of service industry Hotel Syariah Aziza Solo. Methods of data collection in this study using the scale of the scale of religiosity and work loyalty scale. The result of data analysis by using product-moment correlation is obtained rxy = 0,291 with p = 0,00 (p <0,01), it shows that hypothesis accepted, that there is a very significant positive relation between religiosity with employee work loyalty. The religiosity of the subjects is very high, the loyalty level of research subjects is high, while the effective contribution of religiosity with job loyalty is 8.47%. Keyword: Commitment Religiosity, employee loyalty, employee in Hotel Syariah Aziza Solo